Euclid VI: NISP-P optical ghosts - Paterson, K.; Schirmer, M.; Okumura, K.; Venemans, B.; Jahnke, K.; Aghanim, N.; Altieri, B.; Amara, A.; Andreon, S.; Baccigalupi, C.; Baldi, M.; Balestra, A.; et al. (EDP Sciences, 2026)
The Near-Infrared Spectrometer and Photometer (NISP) on board Euclid includes several optical elements in its path that introduce artefacts into the data from non-nominal light paths. To ensure uncontaminated source photometry, these artefacts must be accurately accounted for. This paper focuses on two specific optical features in NISP's photometric data (NISP-P): ghosts caused by the telescope's dichroic beamsplitter, and the bandpass filters within the NISP fore-optics. Both ghost types exhibit a characteristic morphology and are offset from the originating stars. The offsets are well modelled using 2D polynomials; only stars brighter than approximately 10 magnitudes in each filter produce significant ghost contributions. The masking radii for these ghosts depend on both the source-star brightness and the filter wavelength, ranging from 20 to 40 pixels. We present the final relations and models used in the near-infrared (NIR) processing function (PF) to mask these ghosts for Euclid's Quick Data Release (Q1).